The Influence of the “My Safety Matters” Poster Media on Understanding Sexual Violence Prevention in Early Childhood - Al Alifa, Izzatun Nafsi; Herman , Herman; Ilyas , Sitti Nurhidayah (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2025)
This study was designed to evaluate the impact of using the ‘My Safety Matters’ poster media on early childhood understanding of sexual violence prevention at Muthmainnah Kindergarten. Sexual violence in children is a serious issue that requires early education. The interactive visual media ‘My Safety Matters’ was created to present self-safety information in a way that is easy for children to understand. This study aims to examine the effect of using the ‘My Safety Matters’ poster media on early childhood understanding of sexual violence prevention. The focus of the study is on children’s ability to recognise their identity, private body parts, good and bad touch, and ways to protect themselves. This study uses a quantitative method with a quasi-experimental design, involving 28 early childhood children at Muthmainnah Kindergarten as the total sample. Data were collected through observation, tests, and documentation. There was a significant difference in understanding between the experimental and control groups after the intervention. The data were analysed using descriptive statistics and the Wilcoxon Signed Rank Test version 25 to determine the difference in children's understanding. The average understanding in the experimental group increased to 27.14, while the control group rose to 20.36. Statistical tests (sig. value 2-tailed 0.000) confirmed a significant effect. In conclusion, the ‘My Safety Matters’ poster media proved effective in increasing children's understanding of sexual violence prevention.